PEMBEBANAN HAK TANGGUNGAN PADA PERJANJIAN PEMBIAYAAN DENGAN AKAD MUDHARABAH DAN KORELASINYA DENGAN AKTA PEMBERIAN HAK TANGGUNGAN YANG DIBUAT OLEH PEJABAT PEMBUAT AKTA TANAH - , Dewa Putu Dipta Dadia Nugraha, Prof. Dr. Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Mudharabah Agreementof financingis oneof theIslamic bankingproductsin theareas ofdistribution offunds, whereineachdistributionof fundsmust observethe principleof prudence. Oneform ofthe application ofthe precautionary principleisthecollateral. The purposeofthisstudywasto determinewhether theagreementof financingcan bechargedbymortgageandwhetherAPHTthattherecanbe madeon the basisof financingagreements. Inthis study, thedatausedaresecondarydataobtainedfromthe researchliteraturethroughprimarylegalmaterials, legal materialssecondaryandtertiarylegal materials.Implementation ofthis studyusinga normativejuridicalmethodthat iswherethe researchfocus more ontheresearchliteratureandlegislation. ImpositionMortgagefinancing isinagreementaccording toMortgageLawNo.4of1996isallowed, becausedebtfinancing isin case ofmoralhazardarisefrommudharibandthisis possibleif youlookat thedebtarisingonpropertymanagement agreement withpeople who have notadultorunderguardianship, in whichagreementcan bechargedaccordingUUHTmortgage.APHTas adeedtothe imposition ofMortgage can be used to charge of financing agreements mudharabah, because APHT requires basic agreement on which the assignment already exists at the time of manufacture APHT by PPAT. But the author does not agree with the editors âdebts agreement" because mudharabah agreement is not an agreement of financing debts.